The prognostic value of high sensitivity troponin T 7 weeks after an acute coronary syndrome. Issue 15 (11th June 2012) - Ang, Donald S C; Kao, Michelle P C; Dow, Ellie; Lang, Chim; Struthers, Allan
Abstract : Objective: The role of high sensitivity troponin T (hs-TnT) in the convalescence phase after an acute coronary syndrome (ACS) is unknown. The authors aim to assess the prognostic utility of a single hs-TnT level at 7-week post-ACS. Second, the authors evaluated whether any serial changes in hs-TnT between the index admission and 7 weeks post-ACS had any link with the prognosis. Third, the authors assessed whether the prognostic utility of hs-TnT is independent of various echocardiographic abnormalities. Methods: The authors measured hs-TnT levels in 326 consecutive patients at 7 weeks after an ACS event. The composite end point of death from any cause or acute myocardial infarction was evaluated over a median duration of 30 months. Results: A high 7-week hs-TnT (>14 ng/l) predicted adverse clinical outcomes independent of conventional risk factors, left ventricular dysfunction and left ventricular hypertrophy on echocardiography (adjusted RR: 2.69 (95% CI 1.45 to 5.00)). Patients with persistent hs-TnT elevation at 7 weeks were also at an increased risk of cardiovascular events compared with those with an initial high hs-TnT which then normalised (unadjusted RR 3.39 (95% CI 2.02 to 5.68)). Conclusion: The authors have demonstrated the prognostic utility of a single 7-week hs-TnT measurement in routine ACS patients and that it could be used to assist medium term risk stratification in this patient cohort. In addition, the authors also showed that hs-TnT predicted long-term adverse prognosis independent of various echo parameters. Future studies should evaluate whether tailoring specific treatment interventions to higher risk individuals as identified by an elevated hs-TnT during the convalescence phase of ACS would improve clinical outcomes.